Initial encounter and discharge disposition of Medicare beneficiaries with post-stroke dysphagia - Jacobs, Molly; Lindrooth, Richard C.; Perraillon, Marcelo C.; Hegland, Karen; McGowan, Robert; Ellis, Charles (Frontiers in Stroke, 2025)
IntroductionDysphagia or disordered swallowing is a post-stroke condition that requires early intervention to improve stroke recovery. Individuals with dysphagia require specialized services to support nutrition and reduce the likelihood of pneumonia after stroke. This study was designed to utilize Medicare claims data to better understand the acute and post-acute pathways of stroke patients with dysphagia.MethodsData included 100% of fee-for-service (FFS) Medicare claims for home health agency (HHA), skilled nursing facility (SNF), inpatient, outpatient, and carrier files. The sample included Medicare beneficiaries who incurred an inpatient claim between January 1, 2016, and October 1, 2019, with ischemic or hemorrhagic stroke as the primary diagnosis.ResultsWe identified 745,917 unique FFS Medicare beneficiaries with a primary stroke diagnosis; 90% were over age 65. Approximately 79% were non-Hispanic White, 12% were Black/African American, and 6% were Hispanic. Among those identified stroke survivors, 32.5% were diagnosed with dysphagia within 90 days, with slight racial/ethnic variations. Between 68% and 73% of people with dysphagia (PWD) had their initial service encounter in an inpatient hospital facility, 15%−16% in an SNF, and 4%−5% in an outpatient facility, and there was little variation across race/ethnicity. Approximately 10%−12% of PWD were discharged directly home, 32%−36% were discharged to an SNF, and 33%−36% were discharged to a long-term care or rehabilitation facility.DiscussionIn this study of Medicare data, the rate of dysphagia after stroke among Medicare beneficiaries was 33%. This rate showed only slight variation across racial and ethnic groups. Approximately 70% of PWD were identified in inpatient settings. Only a small percentage (10%) were discharged home, with 80% moving to facilities offering rehabilitative services (SNF, long-term care, or rehabilitation facility).